THE CORRUPTING POWER OF SLAVERY IN HARRIET ANN JACOB’S INCIDENTS IN THE LIFE OF A SLAVE GIRL - Asst. Prof. Dr. Mohammad Naji Hussain, Instructor Mr. Maytham Ali Khalefa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The American society during the nineteenth century illustrates in a great picture the suffering of the black Americans due to the oppression, bondage, and capitalism. The black experience of slavery in America begins with the enforced transportation of thousands of Africans across the Atlantic to America mainly in the North. The slaves survived on a very basic diet and their clothing and housing could at best be described as adequate. Also they worked very hard with little opportunity to release the pressure of their lives. The black experience of slavery in North America is one of great suffering.This study aims to find out how Harriet Ann Jacobs in a realistic way portray her life and the lives of several women under the evil of slavery and it spots light on the aspects of this phenomenon that goes parallel with racial discrimination, bad treatment and sexual abuse. So, by studying this particular narrative about the southern slave system, the research is going to have good understanding of not only the community of southern slaves but also American society as awhole.